Eko-Etika Menurut Laudato-Si’ Artikel 138-141 Sebagai Upaya Mengatasi Krisis Ekologis di Indonesia - Ton, Sekundus Septo Pigang (Proceedings of The National Conference on Indonesian Philosophy and Theology, 2025)
The focus of this article is to examine eco-ethics according to the encyclical Laudato-Si articles 138-141 as an effort to overcome the ecological crisis in Indonesia. Indonesia is experiencing an ecological crisis as a result of irresponsible human behavior in utilizing natural resources. The findings of this article are first, there needs to be ethics (transcendental awareness) in relating to organisms, in order to create order in the ecosystem. Second, destroying the universe is the same as destroying oneself because the ecosystem is a place of survival, if its balance is disturbed, it will also have an impact on human welfare. Third, nature as a life giver, natural resources play an important role in various aspects of life. Fourth, humans come from nature and return to nature. The role of the government is needed to issue strict laws. Also the role of society and non-governmental organizations (NGOs) and international cooperation in overcoming the global ecological crisis. The method used is a literature review with descriptive analysis. With this method, the team of writers found four contributions in the 4 numbers of the encyclical article concerned, namely in the form of eco-ethical values.AbstrakFokus penulisan artikel ini adalah menelaah eko-etika menurut ensiklik Laudato-Si artikel 138-141 sebagai sebuah upaya untuk mengatasi krisis ekologis di Indonesia. Indonesia tengah mengalami krisis ekologi sebagai akibat dari perilaku manusia yang tidak bertanggung jawab dalam memanfaatkan hasil alam. Temuan dari penulisan artikel ini adalah pertama, perlu ada etika (kesadaran transendental) dalam berelasi dengan organisme, agar terciptanya keteraturan dalam ekosistem tersebut. Kedua, merusak alam semesta sama dengan menghancurkan diri karena ekosistem adalah wadah kelangsungan hidup, apabila terganggu keseimbangannya maka berdampak juga pada kesejahteraan manusia. Ketiga, alam sebagai pemberi hidup, sumber daya alam memainkan peran penting dalam berbagai aspek kehidupan. Keempat, manusia berasal dari alam dan kembali ke alam. Peran pemerintah dibutuhkan untuk menerbitkan hukum yang tegas. Juga peran masyarakat dan Lembaga Swadaya Masyarakat (LSM) dan kerjasama internasional dalam mengatasi krisis ekologis global. Metode yang digunakan adalah kajian pustaka dengan analisis deskriptif. Dengan metode ini, tim penulis menemukan empat sumbangsih dalam 4 nomor artikel ensiklik bersangkutan, yaitu berupa nilai eko-etis.